A descriptive study of blood pressure in people with self-reported substance use seeking health care in region F, Johannesburg, South Africa - K.E. Oladimeji; S. Gumede; A. Nyatela; S. Nonyukela; R. Mohale; S.T. Lalla-Edward; D. Dwarka (Preventive Medicine Reports)
Background: Elevated blood pressure is a major risk factor for cardiovascular diseases like hypertension and leading cause of death in sub-Saharan Africa. Substance use such as alcohol, tobacco and drugs, is one of various factors attributable to elevated blood pressure This study describes the prevalence of elevated blood pressure and associated factors among individuals who self-reported to substance use. Methods: This descriptive cross-sectional study involved use of secondary data from the Integrating HIV and Heart Health in South Africa study collected between August 2022 to May 2024. Primary outcome, elevated blood pressure was classified as systolic blood pressure ≥ 140 mmHg, and diastolic blood pressure ≥ 90 mmHg. Data was analysed using STATA version 17. Logistic regression analysis was performed to identify factors associated with elevated blood pressure. Results: Of the 2148 participants included, 57.3 % (1230/2148) were males. The participants' median age was 41 years, and 35.9 % (772/2148) had elevated blood pressure, however only 16,9 % of the participants were receiving anti-hypertensive treatment. Independent factors associated with elevated blood pressure were increasing age - 30-39 years old (adjusted odds ratio (aOR) 2.78 [95 %CI 1.42–5.41], 40–49 years old (aOR 3.81 [95 %CI 1.95–7.46]), 50+ years (aOR 5.00 [95 %CI 2.45–10.20] and having comorbidities (aOR 2.35 [95 %CI 1.31–4.22]). Conclusions: Prevalence of elevated blood pressure was high and only a few of these were on anti-hypertensive treatment. Most participants reported using alcohol, including both alcohol and tobacco concurrently. Findings highlight the need for substance use interventions as part of cardiovascular disease management strategies.